Peran Strategis Kompetensi Sosial Guru dalam Membangun Lingkungan Belajar yang Inklusif dan Humanis - Lara Santri; Putri Yulianisa; Deni Supriadi Duha; Ade Irma (CV. Lentera Literasi Indonesia, 2026)
Teachers' social competence is an important component in creating an inclusive, humanistic, and collaborative learning environment. This article aims to analyze the strategic role of teachers' social competence based on field studies through interviews with teachers at SMAN 1 Tambang, MTs Basma Darul'ilmi Wassa'adah, and SMPN 23 Pekanbaru. This study employs a qualitative approach with a descriptive research design. The approach aims to gain an in-depth understanding of the phenomenon under investigation based on participants’ perspectives within a natural setting. Data were collected through in-depth interviews, observations, and documentation. The collected data were analyzed using an interactive analysis technique, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings indicate that teachers with high social competencies are able to establish healthy relationships with students, resolve conflicts wisely, collaborate with colleagues, and create inclusive classrooms. These findings align with the humanistic approach in education, which emphasizes the importance of effective communication and social literacy in learning.